2003
DOI: 10.1242/jeb.00655
|View full text |Cite
|
Sign up to set email alerts
|

A role for nitric oxide in hypoxia-induced activation of cardiac KATP channels in goldfish (Carassius auratus)

Abstract: SUMMARY Hypoxia-induced shortening of cardiac action potential duration (APD) has been attributed in mammalian hearts to the activation of ATP-sensitive potassium (KATP) channels. Since KATP channels are also present at high densities in the hearts of vertebrate ectotherms, speculation arises as to their function during periods of reduced environmental oxygen. The purpose of the present study was to determine whether nitric oxide (NO)plays a role in cardiac sarcolemmal KATP channel activation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…In mammals, numerous cellular pathways and end-effectors are involved in preconditioning (Okubo et al, 1999;Nakano et al, 2000;Yellon and Downey, 2003). No experiments have directly investigated the cellular mechanisms that mediate myocardial preconditioning in fishes, although recent studies suggest that sarcolemmal (Cameron et al, 2003) and mitochondrial (MacCormack and Driedzic, 2002) ATPsensitive K + channels, and MAPK signaling pathways (ERK, JNKs and p38-MAPK; Gaitanaki et al, 2003) may be involved.…”
Section: Hypoxic Acclimationmentioning
confidence: 99%
“…In mammals, numerous cellular pathways and end-effectors are involved in preconditioning (Okubo et al, 1999;Nakano et al, 2000;Yellon and Downey, 2003). No experiments have directly investigated the cellular mechanisms that mediate myocardial preconditioning in fishes, although recent studies suggest that sarcolemmal (Cameron et al, 2003) and mitochondrial (MacCormack and Driedzic, 2002) ATPsensitive K + channels, and MAPK signaling pathways (ERK, JNKs and p38-MAPK; Gaitanaki et al, 2003) may be involved.…”
Section: Hypoxic Acclimationmentioning
confidence: 99%
“…Intracellular alteration of Na and calcium concentrations following ATP depletion is associated with activation of inwardly rectifier K channels (KIR) of high conductance, to facilitate cell membrane re-polarization (Lien et al, 2003;Mintert et al, 2007;Harrell et al, 2007;Pouget, 2008). During hypoxia, ischemia or metabolic inhibition, ATP-dependent K channels (K ATP ) open, which facilitate K influx and shortening of action potential duration (Harrell, 2007;Pouget, 2008;Lebuffe et al, 2003;Cameron et al, 2003;Lascano et al, 2002). Therefore, reduced extracellular K concentration, following ATP depletion seems to be due to the activation of ATPdependent KIR channels, located in the membrane of endothelial cells (Cameron et al, 2003;Hu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia, ischemia or metabolic inhibition, ATP-dependent K channels (K ATP ) open, which facilitate K influx and shortening of action potential duration (Harrell, 2007;Pouget, 2008;Lebuffe et al, 2003;Cameron et al, 2003;Lascano et al, 2002). Therefore, reduced extracellular K concentration, following ATP depletion seems to be due to the activation of ATPdependent KIR channels, located in the membrane of endothelial cells (Cameron et al, 2003;Hu et al, 2003). The other explanation for reduced extracellular K concentration might be increased K uptake through Na-K-Cl cotransport, as seen in rat brain capillary endothelial cells (RBECs) under hypoxic conditions (Kawai et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Procedures have been previously described (Cameron et al, 2003); briefly, the entire heart was mounted in a tissue bath and superfused with normoxic saline solution at a rate of 15·ml·min -1 . This solution contained (in mmol·l -1 ) 150 NaCl, 5 KCl, 1.2 NaH 2 PO 4 , 1.2 MgSO 4 , 1.8 CaCl 2 , 10 Hepes and 10 glucose; pH was maintained at 7.6 and temperature held at 21±1°C.…”
Section: Intracellular Recordingmentioning
confidence: 99%
“…In addition, nitric oxide synthase (NOS) has been localized in the hearts of goldfish (Bruning et al, 1996), and NO has been shown to play a critical role, via cGMP, in regulating the heart and peripheral vasculature in a variety of teleost species (Imbrogno et al, 2003;Jennings et al, 2004;Pellegrino et al, 2003). In goldfish, NO synthesized in cardiac myocytes plays a role in sarcK ATP channel activation during moderate hypoxia (Cameron et al, 2003). Although it has been proposed that hypoxia-induced K ATP channel activation, whether in the heart or in the brain, contributes to the enhanced tolerance of environmental oxygen depletion exhibited by many ectothermic vertebrates (Cameron and Baghdady, 1994;Pek-Scott and Lutz, 1998), this possibility has not been directly tested in fish.…”
mentioning
confidence: 99%